The activity of silver nanoparticles (Axonnite) on clinical and environmental strains of Acinetobacter spp. Issue 2 (March 2015) - Łysakowska, Monika E.; Ciebiada-Adamiec, Anna; Klimek, Leszek; Sienkiewicz, Monika
Abstract Acinetobacter baumannii isolates are responsible for a high number of wound infections. The reason of this study was to evaluate the activity of silver nanoparticles obtained by microexplosion against wide range of Acinetobacter spp. Susceptibility to silver nanoparticles was tested by microdilution method, susceptibility to antibiotics was evaluated by the disc-diffusion method. All strains of Acinetobacter spp. were sensitive to AgNPs at low concentrations. The values of the MIC for strains of Acinetobacter spp. were 0.39 and 0.78 μg/mL. In general, strains inhibited by 0.78 μg/mL of AgNPs were more resistant to antibiotics than Acinetobacter strains for which MIC = 0.39 μg/mL (p = 0.023). The AgNPs in Axonnite seems to be a good alternative for other antimicrobials to treat wound infections caused by multidrug resistant Acinetobacter spp. strains because of its high activity.